1989
DOI: 10.1073/pnas.86.6.1914
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism in the formation of a human ring chromosome 21.

Abstract: We have characterized the structural rearrangements of a chromosome 21 that led to the de novo formation of a human ring chromosome 21 [r(21)]. Molecular cloning and chromosomal localization of the DNA regions flanking the ring junction provide evidence for a long arm to long arm fusion in formation of the r(21). In addition, the centromere and proximal long arm region of a maternal chromosome 21 are duplicated in the r(21). Therefore, the mechanism in formation of the r(21) was complex involving two sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
33
0
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
6
33
0
2
Order By: Relevance
“…Significantly, we demonstrate here that the in vivo breakpoint of a previously described chromosomal translocation (31) corresponds to a "hotspot" of in vitro DNA cleavage by Topo II within the MAR of the mouse immunoglobulin K-chain gene. Furthermore, we found that a MAR has been deleted during rabbit immunoglobulin K-chain gene evolution (32) and that MARs reside at the recombination junction of a human ring chromosome 21 adjacent to a long interspersed repetitive element (LINE) (33). These results provide evidence for a dysfunction of MARs in illegitimate recombination, since these sequences are sometimes found at points of DNA insertion, deletion, and translocation.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Significantly, we demonstrate here that the in vivo breakpoint of a previously described chromosomal translocation (31) corresponds to a "hotspot" of in vitro DNA cleavage by Topo II within the MAR of the mouse immunoglobulin K-chain gene. Furthermore, we found that a MAR has been deleted during rabbit immunoglobulin K-chain gene evolution (32) and that MARs reside at the recombination junction of a human ring chromosome 21 adjacent to a long interspersed repetitive element (LINE) (33). These results provide evidence for a dysfunction of MARs in illegitimate recombination, since these sequences are sometimes found at points of DNA insertion, deletion, and translocation.…”
mentioning
confidence: 57%
“…4C). These MARs are separated by a 750-bp region that contains the 3' end of a LINE (33), which resides on a 0.8-kb Nco I fragment that does not exhibit significant binding (Fig. 4 B and C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Topoisomerase II sites also occur near rearrangement breakpoints in the Dystrophin gene (Hu et al, 1991) and ring chromosome 21 (Wong et al, 1989). In vitro and in vivo evidence for the role of topoisomerase II in nonhomologous recombination is well established in prokaryotes (O'Connor et al, 1985;Ikeda, 1986) and a role for vertebrate topoisomerase II in nonhomologous recombination has been demonstrated in vitro (Bae et al, 1988).…”
Section: Somatic Inactivation Of Brc Almentioning
confidence: 97%
“…The human and rodents cell lines, as well as human/ rodent somatic cell hybrids, WALT, 2Fur, ACEM, R2-10, and 21q + cells were used and their properties have been described previously (Oates and Patterson, 1977;Kozak et al, t977;Van Keuren et al, 1986;Patterson et al, 1983;Wong et al, 1989;Drabkin et al, 1895).…”
Section: Methodsmentioning
confidence: 99%